An Epigenome Wide Association Study Reveals Timing of Physical Activity During Pregnancy Is Associated With Placental DNA Methylation. (7th June 2021) - Zhao, Sifang Kathy; Yeung, Edwina; Ouidir, Marion; Hinkle, Stefanie; Grantz, Katherine; Grewal, Jagteshwar; Mitro, Susanna; Wu, Jing; Stevens, Danielle; Chatterjee, Suvo; Tekola-Ayele, Fasil; Zhang, Cuilin
Abstract: Objectives: Physical activity (PA) prior to and during pregnancy may influence offspring health through epigenetic modifications in the placenta. Prior studies had a single PA assessment in pregnancy limiting the ability to account for PA changes during pregnancy. We hypothesized that timing of PA may be associated with differential methylation and evaluated associations between multiple assessments of PA and genome-wide methylation changes in the placenta. Methods: Placental tissues were obtained at delivery and DNA methylation was measured using the Illumina Human Methylation450 Beadchip for 301 mothers in the NICHD Fetal Growth Studies–Singleton cohort. Total PA (metabolic equivalent minutes/week) was assessed using the Pregnancy PA Questionnaire targeted for 8–13 (visit 0), 16–22 (visit 1), 24–29 (visit 2), 30–33 (visit 3), 34–37 (visit 4), 38–41 (visit 5) weeks' gestation. For associations of PA at each visit with methylation, we conducted linear regression adjusting for potential confounders such as maternal age, race/ethnicity, pre-pregnancy body mass index. Genes annotating significant CpG sites (false discovery rate adjusted P < 0.05) were queried for enrichment of functional pathways using Ingenuity Pathway Analysis. Results: PA in the 12 months prior to visit 0 was not significantly associated with methylation, whereas PA since last visit for visits 1–5 were associated with methylation of 1, 0, 2, 29, 30 CpG sites, respectively (P values ranging from 3.07 × 10 −9 to 3.35 × 10 −6 ). Thirteen CpG sites significantly related to PA overlapped at visits 4 & 5, with the most significant associations at cg21385047 located in sphingosine-1-phosphate receptor 1 ( S1PR1, P = 3.07 × 10 −9, P = 7.45 × 10 −9, respectively). Five enriched pathways overlapped at visits 4 & 5 (P < 0.05): inositol pyrophosphates biosynthesis, gustation pathway, choline biosynthesis III, cAMP-mediated signaling, G-protein coupled receptor signaling. Conclusions: Findings suggest that PA during pregnancy is associated with placental DNA methylation changes at loci potentially related to cardiovascular and neurological system development/function. If replicated, our findings could shed light onto the mechanisms underlying changes in offspring epigenetic profile associated with maternal PA. Funding Sources: Eunice Kennedy Shriver National Institute of Child Health and Human Development.